Two Co(II) coordination polymers: crystal structures and treatment activity on myofascial pain syndrome. Issue 6 (3rd June 2022) - Lai, Shangdao; Pan, Meiyuan; Liu, Jiongfeng; Li, Yalan
Abstract: In the current study, two new Co(II)-containing coordination polymers (CPs) with the chemical formulae of [[Co3 (μ4 -cpboda)2 (μ2 -H2 O)2 (DMF)2 (H2 O)2 ]·3DMF·2HCOOH·2H2 O] n (1 ) and [[Co3 (μ 3 -cpboda)2 (1, 4-bib)5 (H2 O)2 ]·DMF] n (2 ) have been successfully prepared via reaction of Co(NO3 )2 ·6H2 O and 3, 3′-((5-carboxy-1, 3-phenylene)bis(oxy))dibenzoic acid (H4 cpboda) without or with the secondary N-donor ligand 1, 4-di(1 H -imidazol-1-yl)benzene (1, 4-bib) under solvothermal conditions. The structural analysis results show that complex 1 features a 2 D layered network which is further extended into the 3 D supramolecular network via H-bond interactions, while complex 2 is a 3 D coordination polymer with a (4, 4, 7)-connected network. The treatment activity of the new compounds on the myofascial pain syndrome (MPS) was evaluated and the mechanism was explored at the same time.